An effective electrocatalyst based on platinum nanoparticles supported with graphene nanoplatelets and carbon black hybrid for PEM fuel cells - Arici, Ece; Kaplan, Begum Yarar; Mert, Ahmet Musap; Gursel, Selmiye Alkan; Kinayyigit, Solen (Pergamon-Elsevier Science Ltd, 2019)
A facile synthesis at room temperature and at solid-state directly on the support yielded small, homogeneous and well-dispersed Pt nanoparticles (NPs) on CB-carbon black, GNPgraphene nanoplatelets, and CB-GNP-50:50 hybrid support. Synthesized Pt/CB, Pt/GNP and Pt/CB:GNP NPs were used as electrocatalysts for polymer electrolyte membrane fuel cell (PEMFC) reactions. HRTEM results displayed very small, homogeneous and well-dispersed NPs with 1.7, 2.0 and 4.2 nm mean-diameters for the Pt/CB-GNP, Pt/GNP and Pt/CB electrocatalysts, respectively. Electrocatalysts were also characterized by RAMAN, XRD, BET and CV techniques. ECSA values indicated better activity for graphene-based supports with 19 m(2) g(Pt)(-1) for Pt/GNP and 55 m(2) g(Pt)(-1) for Pt/CB-GNP compared to 10 m(2)g(Pt)(-1) for Pt/CB. Oxygen reduction reaction (ORR) studies and fuel cell tests were in parallel with these results where highest maximum power density of 377 mW cm(-2) was achieved with Pt/CB-GNP hybrid electrocatalyst. Both fuel cell and ORR studies for Pt/CB-GNP indicated better dispersion of NPs on the support and efficient fuel cell performance that is believed to be due to the prevention of restacking of GNP by CB. To the best of our knowledge, Pt/GNP and Pt/CB-GNP electrocatalysts are the first in literature to be synthesized with the organometallic mild synthesis method using Pt(dba)(3) precursor for the PEMFC applications. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
14th International Conference on Energy Storage (EnerSTOCK) -- APR 25-28, 2018 -- Cukurova Univ, Adana, TURKEY
Keywords: Electrocatalyst; Platinum nanoparticle; PEM fuel cell; Graphene nanoplatelets; Vulcan XC-72